Microplastics have lethal and sublethal effects on stream invertebrates and affect stream ecosystem functioning. (April 2020) - López-Rojo, Naiara; Pérez, Javier; Alonso, Alberto; Correa-Araneda, Francisco; Boyero, Luz
Abstract: Microplastics (MPs) are contaminants of increasing concern due to their abundance, ubiquity and persistence over time. However, knowledge about MP distribution in fresh waters and their effects on freshwater organisms is still scarce, and there is virtually no information about their potential influence on ecosystem functioning. We used a microcosm experiment to examine the effects of MPs (fluorescent, 10-μm polystyrene microspheres) at different concentrations (from 0 to 10 3 particles mL −1 ) on leaf litter decomposition (a key process in stream ecosystems) and associated organisms (the caddisfly detritivore Sericostoma pyrenaicum ), and the extent to which MPs were attached to leaf litter and ingested and egested by detritivores, thus assessing mechanisms of MP trophic transfer. We found that MPs caused detritivore mortality (which increased 9-fold at the highest concentration) but did not affect their growth. Analysis of fluorescence in samples suggested that MPs were rapidly ingested (most likely through ingestion of particles attached to leaf litter) and egested. Leaf litter decomposition was reduced as a result of increasing MP concentrations; the relationship was significant only in the presence of detritivores, but microbially-mediated decomposition showed a similar trend. Our findings provide novel evidence of harmful effects of MPs on aquatic insects and stream ecosystem functioning, and highlight the need for the standardization of methods in future experiments with MPs in order to allow comparisons and generalizations. Graphical abstract: Image 1 Highlights: We examined microplastic (MP) effects on leaf litter decomposition and detritrivore growth. Detritivore mortality increased with MP concentration (0–1800 part. mL −1 ). MPs reduced leaf litter decomposition, affecting ecosystem functioning. MPs were found in detritivore faeces indicating ingestion and egestion. MP adherence to leaf litter suggested they were ingested while feeding.